Low genetic diversities of rabies virus populations within different hosts in Brazil - Kobayashi, Yuki; Suzuki, Yoshiyuki; Itou, Takuya; Carvalho, Adolorata Aparecida Bianco [UNESP]; Cunha, Elenice M. S.; Ito, Fumio H.; Gojobori, Takashi; Sakai, Takeo (Elsevier B.V., 2010)
The low rates of nonsynonymous evolution observed in natural rabies virus (RABV) isolates are suggested to have arisen in association with the structural and functional constraints operating on the virus protein and the infection strategies employed by RABV within infected hosts to avoid strong selection by the immune response. In order to investigate the relationship between the genetic characteristics of RABV populations within hosts and the virus evolution, the present study examined the genetic heterogeneities of RABV populations within naturally infected dogs and foxes in Brazil, as well as those of bat RABV populations that were passaged once in suckling mice. Sequence analyses of complete RABV glycoprotein (G) genes showed that RABV populations within infected hosts were genetically highly homogeneous whether they were infected naturally or experimentally (nucleotide diversities of 0-0.95 x 10(-3)). In addition, amino acid mutations were randomly distributed over the entire region of the G protein, and the nonsynonymous/synonymous rate ratios (d(N)/d(S)) for the G protein gene were less than 1. These findings suggest that the low genetic diversities of RABV populations within hosts reflect the stabilizing selection operating on the virus, the infection strategies of the virus, and eventually, the evolutionary patterns of the virus. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Evolution; Genetic heterogeneity; Low genetic diversity; Rabies virus